Bankruptcy according to the bankruptcy law and postponement of payment perspective of creditor legal protection - Yulianti Wiyono,; Slamet Suhartono,; Endang Prasetyawati, (Technium Social Sciences Journal, 2024)
The development of the business world is strongly influenced by the business world as one of the economic actors, including the banking business. The business world is also very dependent on the conduciveness of the business climate that supports it. If the business climate conditions are not conducive, it will affect the stability of the business world, and can even cause business actors to suffer losses, which results in the capability and credibility of business actors in carrying out their business activities being disrupted, and can even result in bankruptcy. To maintain the smooth running of their business, business actors must obtain guaranteed protection through legal instruments established by the government. Legal protection given to banks as creditors is needed in maintaining business continuity. This legal protection is very important, considering that banking is an economic joint that supports the most vital national economy. Filing for bankruptcy which requires a minimum of 2 (two) creditors for a bankrupt debtor using the Postponement of Debt Payment Obligation mechanism based on the bankruptcy law and PKPU does not provide a guarantee of sufficient legal protection for creditors.